Diagnostic and Predictive Values of Circulating Extracellular Vesicle-Carried microRNAs in Ischemic Heart Disease Patients With Type 2 Diabetes Mellitus - Zhang, Li; Zhang, Jianchao; Qin, Zhen; Liu, Na; Zhang, Zenglei; Lu, Yongzheng; Xu, Yanyan; Zhang, Jinying; Tang, Junnan (Frontiers in Cardiovascular Medicine, 2022)
Ischemic heart disease patients with diabetes mellitus (IHD-DM) have a higher risk of cardiovascular events than those without DM. Rapid identification of IHD-DM can enable early access to medical treatment and reduce the occurrence of cardiovascular adverse events. In the present study, we identified and examined extracellular vesicle (EV)-carried microRNAs (miRNAs) as the possible diagnostic biomarkers of IHD-DM. Small RNA sequencing was performed to analyze the EV-carried miRNAs spectrum, and differentially expressed miRNAs were further confirmed by quantitative real-time polymerase chain reaction (qRT-PCR). Through small RNA sequencing, we identified 138 differentially expressed EV-carried miRNAs between IHD-DM patients and healthy controls. Furthermore, we identified that five EV-carried miRNAs (miR-15a-3p, miR-18a-5p, miR-133a-3p, miR-155-5p, and miR-210-3p) were significantly down-regulated and one (miR-19a-3p) was significantly up-regulated in the IHD-DM patients compared to healthy controls. The receiver–operating characteristic curve analysis showed that the above six EV-carried miRNAs have excellent diagnostic efficacy of IHD-DM. Our findings indicated that the circulating EV-miRNAs might be promising biomarkers for the convenient and rapid diagnosis of IHD-DM.